Biorefining of Pigeon Pea: Residue Conversion by Pyrolysis - Rowena C. Tanquilut, Mari; Genuino, Homer C.; Wilbers, Erwin; Amongo, Rossana Marie C.; Suministrado, Delfin C.; Yaptenco, Kevin F.; Elauria, Marilyn M.; Elauria, Jessie C.; Heeres, Hero J. (Energies (Basel), 2020)
Pyrolysis is an important technology to convert lignocellulosic biomass to a renewable liquid energy carrier known as pyrolysis oil or bio-oil. Herein we report the pyrolysis of pigeon pea wood, a widely available biomass in the Philippines, in a semi-continuous reactor at gram scale. The effects of process conditions such as temperature (400–600 °C), nitrogen flow rate (7–15 mL min−1) and particle size of the biomass feed (0.5–1.3 mm) on the product yields were determined. A Box-Behnken three-level, three-factor fractional factorial design was carried out to establish process-product yield relations. Of particular interest is the liquid product (bio-oil), of which the yield was shown to depend on all independent variables in a complex manner. The optimal conditions for highest bio-oil yield (54 wt.% on dry feed intake) were a temperature of 466 °C, a nitrogen flow rate of 14 mL min−1 and a particle size of 1.3 mm. Validation of the optimized conditions proved that the average (n = 3) experimental bio-oil yield (52 wt.%) is in good agreement with the predicted value from the model. The properties of product oils were determined using various analytical techniques including gas chromatography-mass spectrometry (GC–MS), gel-permeation chromatography (GPC), nuclear magnetic resonance spectroscopy (13C- and HSQC-NMR) and elemental and proximate analyses. The bio-oils were shown to have low ash content (0.2%), high heating value (29 MJ kg−1) and contain high value-added phenolics compounds (41%, GC peak area) as well as low molecular weight aldehydes and carboxylic acids. GPC analysis indicated the presence of a considerable amount of higher molecular weight compounds. NMR measurements showed that a large proportion of bio-oil contains aliphatic carbons (~60%), likely formed from the decomposition of (hemi)cellulose components, which are abundantly present in the starting pigeon pea wood. Subsequent preliminary scale-up pyrolysis experiments in a fluidized bed reactor (~100 gfeed h−1, 475 °C and N2 flow rate of 1.5 L min−1) gave a non-optimized bio-oil yield of 44 wt.%. Further fractionation and/or processing are required to upgrade these bio-oils to biofuels and biobased chemicals.